Exploring the diversity of produced water bacteria with hydrocarbon-degrading potential using MALDI-TOF MS and multivariate statistical analyses - Maryam Al-Kaabi (17986696) (2025)
The success of bioremediation of produced water relies on the use of hydrocarbon-degrading bacteria. Hence, the selection of highly tolerant endogenous strains from produced water is crucial to designing successful bioremediation. However, the employed isolation and screening approaches are, in general, long. Integrative and rapid approaches based on microbiological and molecular techniques are now required due to the frequent fluctuation of the composition of the produced water. Here, enrichment cultures at high toxicity followed by protein profiling using MALDI-TOF MS were shown to be efficient in clustering the endogenous hydrocarbon-degrading bacteria and help select the potential candidates. Several bacterial strains ( n= 18) were isolated from produced water sampled from Qatar’s North Field natural gas production. Fourteen strains were identified as Bacillus cereus ( n= 14), and one as Staphylococcus hominis ( n= 1) using MALDI-TOF MS. Three strains were identified as Aneurinibacillus humi ( n= 2) and Aneurinibacillus aneurinilyticus ( n= 1) through ribotyping. The strains were further differentiated based on their protein profiles using MALDI-TOF MS and multivariate statistical analyses. Multivariate analyses (composite correlation index, principal component analysis, and dendrogram) demonstrated substantial diversity among the isolates, highlighting their potential as robust candidates for bioremediation and produced water treatment. Other Information Published in: Biotechnology Letters License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10529-025-03641-0